Beyond drought : people, policy and perspectives - Fisher, Melanie; Botterill, Linda Courtenay (CSIRO ; Eurospan, 2003)
Australia is the only country on the planet that has a non-annual climate cycle and this poses real challenges for an agricultural sector based on practices which were developed for the relative predictability of a European climate. Since 1989 official Government policy in Australia has moved towards acceptance of this reality and rejected the notion that drought is a natural disaster in favour of a policy approach based on risk management.